Tuning Viscoelasticity in Alginate Hydrogels for 3D Cell Culture Studies. Issue 5 (17th May 2021) - Charbonier, Frank; Indana, Dhiraj; Chaudhuri, Ovijit
Abstract: Physical properties of the extracellular matrix (ECM) affect cell behaviors ranging from cell adhesion and migration to differentiation and gene expression, a process known as mechanotransduction. While most studies have focused on the impact of ECM stiffness, using linearly elastic materials such as polyacrylamide gels as cell culture substrates, biological tissues and ECMs are viscoelastic, which means they exhibit time‐dependent mechanical responses and dissipate mechanical energy. Recent studies have revealed ECM viscoelasticity, independent of stiffness, as a critical physical parameter regulating cellular processes. These studies have used biomaterials with tunable viscoelasticity as cell‐culture substrates, with alginate hydrogels being one of the most commonly used systems. Here, we detail the protocols for three approaches to modulating viscoelasticity in alginate hydrogels for 2D and 3D cell culture studies, as well as the testing of their mechanical properties. Viscoelasticity in alginate hydrogels can be tuned by varying the molecular weight of the alginate polymer, changing the type of crosslinker—ionic versus covalent—or by grafting short poly(ethylene‐glycol) (PEG) chains to the alginate polymer. As these approaches are based on commercially available products and simple chemistries, these protocols should be accessible for scientists in the cell biology and bioengineering communities. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Tuning viscoelasticity by varying alginate molecular weight Basic Protocol 2 : Tuning viscoelasticity with ionic versus covalent crosslinking Basic Protocol 3 : Tuning viscoelasticity by adding PEG spacers to alginate chains Support Protocol 1 : Testing mechanical properties of alginate hydrogels Support Protocol 2 : Conjugating cell‐adhesion peptide RGD to alginate